Hexagonal Boron Nitride Single Crystal Thermal Oxidation and Etching in Air: An Atomic Force Microscopy Study. (2nd January 2019) - Khan, N.; Nour, E.; Mondoux, J.; Liu, S.; Edgar, J.H.; Berta, Y.
ABSTRACT: Hexagonal boron nitride (hBN), a two dimensional (2D) material, has emerged as an important substrate and dielectric for electronic, optoelectronic, and photonic devices based on graphene and other atomically thin two dimensional materials. Here we report on the initial oxidation of (0001) hBN single crystals in ambient air as functions of temperature and time, as determined by atomic force microscopy (AFM) and scanning electron microscope with energy dispersive X-ray spectroscopy (SEM/EDS). For oxidation times of 20 minutes, the first evidence of oxidation appears at 900°C, with the formation of shallow, hexagonal-, and irregular-shaped pits that are less than 100 nm across and several nanometer deep. Oxidation at 1100°C for 20 minutes produced 1.0-2.0-micron size pits with flat and pointed bottoms that were approximately hexagonal-shaped, but with rough and irregular edges, and multiple interior steps. Oxidation was not uniform on the surface of hBN, but starts where dislocations in the crystal intersected the surfaces. Pit depth increased linearly with temperature and oxidation times. In addition to the surface pits, small particles formed on the surface. Elemental analysis of the thermally oxidized hBN crystals by SEM/EDS revealed the major elements of these particles were boron and oxygen.